The effect of smoking on periodontal treatment response: a review of clinical evidence - L. Heasman (journal of clinical periodontology, 2006)
Background: Smoking has been identified as a significant risk factor for periodontal diseases and is regarded as being responsible for incomplete or delayed healing in patients following treatment. Aim and Method: The aim of this conventional review was to review, collate and tabulate the relative effectiveness of treatments of chronic periodontitis in smokers, non-smokers and ex-smokers. Observations: The majority of clinical trials show significantly greater reductions in probing depths and bleeding on probing, and significantly greater gain of clinical attachment following non-surgical and surgical treatments in non-smokers compared with smokers. This benefit is also seen at class I and II furcation sites and in patients prescribed systemic or local antimicrobial treatments. Conclusions: Data from epidemiological, cross-sectional and case–control studies strongly suggest that quitting smoking is beneficial to patients following periodontal treatments. The periodontal status of ex-smokers following treatment suggests that quitting the habit is beneficial although there are only limited data from long-term longitudinal clinical trials to demonstrate unequivocally the periodontal benefit of quitting smoking.